Lithium ion secondary battery, electric device, and positive electrode material
Patent Information
- Application Number
- CN202510494330.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2026-10-23
AI Technical Summary
[0041]在一些实施方式中,正极材料的振实密度为1.4g/cc~1.8g/cc。由此,有利于提高正极材料的致密性,进而有利于提高电池的充放电效率。
Smart Images

Figure CN122968381A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a lithium-ion secondary battery, an electrical device, and a positive electrode material. Background Technology
[0002] In recent years, with the increasingly wide application of secondary batteries, they have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, aerospace, and many other fields. With the rapid development of secondary batteries, higher requirements have been placed on their kinetic performance and energy density.
[0003] Therefore, how to make secondary batteries have excellent kinetic performance and energy density has become an urgent technical problem to be solved. Summary of the Invention
[0004] This application is made in view of the above-mentioned problems, and its purpose is to provide a lithium-ion secondary battery, an electrical device, and a positive electrode material. The lithium-ion secondary battery prepared in this application has excellent kinetic performance and energy density.
[0005] To achieve the above objectives, the first aspect of this application provides a lithium-ion secondary battery, including a positive electrode sheet. The positive electrode sheet includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector and including a positive electrode material. The positive electrode material includes a lithium transition metal oxide, which includes nickel, cobalt, and M elements. The M element includes manganese and / or aluminum elements. Based on the total molar number of nickel, cobalt, and M elements, the molar percentage of nickel is greater than or equal to 50% and less than 100%. The lithium transition metal oxide includes primary particles with a particle size of 0.5 μm to 6 μm. Based on the total number of primary particles with a particle size of 0.5 μm to 6 μm, the number of primary particles with a particle size of 0.5 μm to 2 μm accounts for 86% to 93%.
[0006] In this application, by controlling the molar proportion of nickel to be greater than or equal to 50% and less than 100%, the energy density of the secondary battery can be improved. By controlling the particle size of the primary particles within the above range, on the one hand, the diffusion distance of lithium ions can be shortened, the migration rate of lithium ions can be increased, and the kinetic performance of the secondary battery can be improved; on the other hand, the compaction density of the material can be increased, further improving the energy density of the secondary battery. In addition, based on the total number of primary particles with a particle size of 0.5μm to 6μm, the proportion of primary particles with a particle size of 0.5μm to 2μm in the cathode material is within the above range, reflecting that the particle size of the primary particles in the cathode material is mostly distributed between 0.5μm and 2μm, and the overall particle size of the cathode material is relatively small. This results in a shorter lithium ion transport path, which can further improve the kinetic performance of the cathode material, thereby increasing the energy density of the secondary battery.
[0007] In some implementations, based on the total number of primary particles with a diameter of 0.5 μm to 6 μm, the proportion of primary particles with a diameter greater than 2 μm is 7% to 14%. This reflects that there are fewer particles with larger diameters in the cathode material, that is, the overall particle size of the cathode material is relatively small, which is beneficial to improving the kinetic performance of the secondary battery, thereby improving the energy density of the battery.
[0008] In some implementations, based on the total number of primary particles with a diameter of 0.5 μm to 6 μm, the proportion of primary particles with a diameter greater than 3 μm is less than 5%. This reflects that there are fewer particles with larger diameters and the particle size distribution is more concentrated in the cathode material, which is beneficial to improving the kinetic performance of the secondary battery, thereby further improving the energy density of the battery.
[0009] In some embodiments, the lithium transition metal oxide further includes modifying elements, including one or more of Mo, W, Nb, Sb, and V. These modifying elements can specifically adsorb onto the (012) and (104) crystal planes, inhibiting their growth. This allows for control of the proportions of the (012) and (104) crystal planes within appropriate ranges, which is beneficial to the kinetic performance of the secondary battery.
[0010] In some embodiments, the modified element accounts for 0.2% to 1% of the mass of the lithium transition metal oxide. This allows the proportions of the (012) and (104) crystal planes to be within a suitable range, which is beneficial to improving the kinetic performance of the secondary battery.
[0011] In some embodiments, the cathode material is analyzed by X-ray diffraction to obtain the integrated area A of the (003) crystal plane. (003) The integral area A of the (101) crystal plane (101) The integral area A of the (012) crystal plane (012)And the integral area A of the (104) crystal plane (104) Satisfy: 20% ≤ A (104) / (A (003) +A (101) +A (012) +A (104) The percentage is ≤50%. This improves the reversible insertion and extraction of lithium ions, thereby enhancing the kinetic performance of the secondary battery.
[0012] In some embodiments, the cathode material is analyzed by X-ray diffraction to obtain the integrated area A of the (003) crystal plane. (003) The integral area A of the (101) crystal plane (101) The integral area A of the (012) crystal plane (012) And the integral area A of the (104) crystal plane (104) Satisfy: 3.5% ≤ A (012) / (A (003) +A (101) +A (012) +A (104) The percentage is ≤5.5%. This improves the reversible insertion and extraction of lithium ions, thereby enhancing the kinetic performance of the secondary battery.
[0013] In some embodiments, when the negative electrode material of the lithium-ion secondary battery is graphite, when the lithium-ion secondary battery is charged and discharged at a current of 0.1C within a voltage range of 2.8V to 4.3V, the obtained capacity-voltage differential dQ / dV curve shows a first oxidation peak and a first reduction peak in the 3.60V to 3.80V range, and a second oxidation peak and a second reduction peak in the 4.15V to 4.25V range. Therefore, the presence of the first oxidation peak, the first reduction peak, the second oxidation peak, and the second reduction peak in the dQ / dV curve reflects a reversible charge-discharge reaction of the positive electrode material, indicating that the positive electrode material has good structural stability.
[0014] In some embodiments, the absolute value ΔV1 of the difference between the peak voltage of the first oxidation peak and the peak voltage of the first reduction peak is less than or equal to 0.06V; and / or, the absolute value ΔV2 of the difference between the peak voltage of the second oxidation peak and the peak voltage of the second reduction peak is less than or equal to 0.08V. The small differences between the oxidation and reduction peaks in both voltage ranges indicate good electrochemical reversibility and low polarization of the cathode material, reflecting good kinetic performance of the secondary battery.
[0015] In some embodiments, the lithium-ion secondary battery includes one or more of the following features:
[0016] (1) Based on the total molar number of nickel, cobalt, and M elements, the molar proportion of nickel is 80% to 92%. Therefore, the high nickel content in the cathode material is beneficial to improving the energy density of the secondary battery;
[0017] (2) Based on the total molar number of nickel, cobalt, and M elements, the molar proportion of cobalt is 4% to 12%. Therefore, it is possible to reduce costs without affecting the conductivity of the cathode material;
[0018] (3) Based on the total molar number of nickel, cobalt and M elements, the molar percentage of M element is 5% to 15%. This is beneficial to the stability and safety performance of the secondary battery.
[0019] In some implementations, the cathode material satisfies one or more of the following characteristics:
[0020] (1) 0.5μm≤Dv2≤1.4μm; (2) 2μm≤Dv50≤3μm; (3) 7μm≤Dv99≤10μm. This is beneficial for balancing the capacity and cycle stability of the cathode material.
[0021] In some implementations, the compaction density of the cathode material is 3.0 g / cm³ under a pressure of 4T. 3 ~3.4g / cm 3 This is beneficial for improving the energy density of lithium-ion secondary batteries.
[0022] In some embodiments, the tap density of the cathode material is 1.4 g / cc to 1.8 g / cc. This is beneficial for improving the compactness of the cathode material, and thus for improving the charge and discharge efficiency of the battery.
[0023] A second aspect of this application provides an electrical device comprising the lithium-ion secondary battery described in the first aspect.
[0024] A third aspect of this application provides a cathode material comprising a lithium transition metal oxide, wherein the lithium transition metal oxide comprises nickel, cobalt, and M, wherein the M comprises manganese and / or aluminum, and the molar percentage of nickel is greater than or equal to 50% and less than 100% based on the total molar number of nickel, cobalt, and M, and the lithium transition metal oxide comprises primary particles with a particle size of 0.5 μm to 6 μm, wherein the number of primary particles with a particle size of 0.5 μm to 2 μm accounts for 86% to 93% based on the total number of primary particles with a particle size of 0.5 μm to 6 μm.
[0025] In this application, by controlling the nickel content to be greater than or equal to 50% and less than 100%, the energy density of the secondary battery can be improved. By controlling the particle size of the primary particles within the above range, on the one hand, the diffusion distance of lithium ions can be shortened, the migration rate of lithium ions can be increased, and the kinetic performance of the secondary battery can be improved; on the other hand, the compaction density of the material can be increased, further improving the energy density of the secondary battery. In addition, the proportion of primary particles with a particle size of 0.5μm to 2μm in the cathode material is within the above range, reflecting that the particle size of the primary particles in the cathode material is mostly distributed between 0.5μm and 2μm, and the overall particle size of the cathode material is relatively small. This results in a shorter lithium ion transport path, which can further improve the kinetic performance of the cathode material, thereby increasing the energy density of the secondary battery.
[0026] In some implementations, based on the total number of primary particles with a diameter of 0.5 μm to 6 μm, the proportion of primary particles with a diameter greater than 2 μm is 7% to 14%. This reflects that there are fewer particles with larger diameters in the cathode material, that is, the overall particle size of the cathode material is relatively small, which is beneficial to improving the kinetic performance of the secondary battery, thereby improving the energy density of the battery.
[0027] In some implementations, based on the total number of primary particles with a diameter of 0.5 μm to 6 μm, the proportion of primary particles with a diameter greater than 3 μm is less than 5%. This reflects that there are fewer particles with larger diameters in the cathode material and the particle size distribution is more concentrated, meaning that the overall particle size of the cathode material is relatively small, which is more conducive to improving the kinetic performance of the secondary battery, thereby further improving the energy density of the battery.
[0028] In some embodiments, the lithium transition metal oxide further includes modifying elements, including one or more of Mo, W, Nb, Sb, and V. These modifying elements can specifically adsorb onto the (012) and (104) crystal planes, inhibiting the growth of the (012) and (104) crystal planes, thereby controlling the proportion of the (012) and (104) crystal planes within a suitable range, which is beneficial to the kinetic performance of the secondary battery.
[0029] In some embodiments, the modified element accounts for 0.2% to 1% of the mass of the lithium transition metal oxide. This allows the proportions of the (012) and (104) crystal planes to be within a suitable range, which is beneficial to improving the kinetic performance of the secondary battery.
[0030] In some embodiments, the cathode material is analyzed by X-ray diffraction to obtain the integrated area A of the (003) crystal plane. (003) The integral area A of the (101) crystal plane (101) The integral area A of the (012) crystal plane (012)And the integral area A of the (104) crystal plane (104) Satisfy: 20% ≤ A (104) / (A (003) +A (101) +A (012) +A (104) The percentage is ≤50%. This improves the reversible insertion and extraction of lithium ions, thereby enhancing the kinetic performance of the secondary battery.
[0031] In some embodiments, the cathode material is analyzed by X-ray diffraction to obtain the integrated area A of the (003) crystal plane. (003) The integral area A of the (101) crystal plane (101) The integral area A of the (012) crystal plane (012) And the integral area A of the (104) crystal plane (104) Satisfy: 3.5% ≤ A (012) / (A (003) +A (101) +A (012) +A (104) The percentage is ≤5.5%. This improves the reversible insertion and extraction of lithium ions, thereby enhancing the kinetic performance of the secondary battery.
[0032] In some embodiments, when a lithium-ion secondary battery assembled from a cathode material and graphite is charged and discharged at a current of 0.1C within a voltage range of 2.8V to 4.3V, the obtained capacity-voltage differential dQ / dV curves show a first oxidation peak and a first reduction peak in the 3.60V to 3.80V range, and a second oxidation peak and a second reduction peak in the 4.15V to 4.25V range. This reflects the existence of a reversible charge-discharge reaction in the cathode material and indicates that the cathode material possesses good structural stability.
[0033] In some embodiments, the absolute value ΔV1 of the difference between the peak voltage of the first oxidation peak and the peak voltage of the first reduction peak is less than or equal to 0.06V; and / or, the absolute value ΔV2 of the difference between the peak voltage of the second oxidation peak and the peak voltage of the second reduction peak is less than or equal to 0.08V. This indicates that the cathode material has good electrochemical reversibility, reflecting good kinetic performance of the secondary battery.
[0034] In some embodiments, the lithium-ion secondary battery includes one or more of the following features:
[0035] (1) Based on the total molar number of nickel, cobalt, and M elements, the molar proportion of nickel is 80% to 92%. Therefore, the high nickel content in the cathode material is beneficial to improving the energy density of the secondary battery;
[0036] (2) Based on the total molar number of nickel, cobalt, and M elements, the molar proportion of cobalt is 4% to 12%. Therefore, it is possible to reduce costs without affecting the conductivity of the cathode material;
[0037] (3) Based on the total molar number of nickel, cobalt and M elements, the molar percentage of M element is 5% to 15%. This is beneficial to the stability and safety performance of the secondary battery.
[0038] In some implementations, the cathode material satisfies one or more of the following characteristics:
[0039] (1) 0.5μm≤Dv2≤1.4μm; (2) 2μm≤Dv50≤3μm; (3) 7μm≤Dv99≤10μm. This is beneficial for balancing the capacity and cycle stability of the cathode material.
[0040] In some implementations, the compaction density of the cathode material is 3.0 g / cm³ under a pressure of 4T. 3 ~3.4g / cm 3 This is beneficial for improving the energy density of lithium-ion secondary batteries.
[0041] In some embodiments, the tap density of the cathode material is 1.4 g / cc to 1.8 g / cc. This is beneficial for improving the compactness of the cathode material, and thus for improving the charge and discharge efficiency of the battery. Attached Figure Description
[0042] Figure 1 This is a schematic diagram of a battery cell according to one embodiment of this application.
[0043] Figure 2 yes Figure 1 An exploded view of a battery cell according to one embodiment of this application is shown.
[0044] Figure 3 This is a schematic diagram of a battery module according to one embodiment of this application.
[0045] Figure 4 This is a schematic diagram of a battery pack according to one embodiment of this application.
[0046] Figure 5 yes Figure 4 An exploded view of a battery pack according to one embodiment of this application is shown.
[0047] Figure 6 This is a schematic diagram of an electrical device that uses a secondary battery as a power source according to one embodiment of this application.
[0048] Figure 7 This is a scanning electron microscope image of the positive electrode material in Embodiment 1 of this application.
[0049] Figure 8 This is the dQ / dV curve of the lithium-ion secondary battery in Example 1 of this application.
[0050] Explanation of reference numerals in the attached figures:
[0051] 1 Battery pack; 2 Upper housing; 3 Lower housing; 4 Battery module; 5 Battery cell; 51 Housing; 52 Electrode assembly; 53 Top cover assembly. Detailed Implementation
[0052] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the lithium-ion secondary battery, power supply device, and positive electrode material of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0053] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0054] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0055] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0056] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0057] Unless otherwise specified, the terms used in this application have the common meanings as commonly understood by those skilled in the art.
[0058] Unless otherwise specified, the values of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, for example, according to the testing methods given in this application.
[0059] Ternary materials are among the most commonly used cathode materials. As the requirements for energy density increase, the nickel content in ternary materials continues to rise, while the cobalt content continues to decline. The decline in cobalt content leads to increasingly poor lithium-ion insertion / extraction kinetics in ternary materials.
[0060] Currently, related technologies improve the kinetic properties of high-nickel, low-cobalt ternary materials by coating fast ion conductors or oxides. However, the bonding force between the coating layer and the high-nickel, low-cobalt material is weak, and the coating layer is prone to detachment as the number of cycles increases, which cannot stably improve the kinetic properties of high-nickel, low-cobalt ternary materials.
[0061] Based on this, this application provides a lithium-ion secondary battery, an electrical device, and a positive electrode material. The lithium-ion secondary battery prepared in this application has excellent kinetic performance and energy density.
[0062] Lithium-ion secondary batteries
[0063] The first aspect of this application provides a lithium-ion secondary battery, which includes a positive electrode sheet, a positive current collector, and a positive electrode film layer disposed on at least one side of the positive current collector and including a positive electrode material. The positive electrode material includes a lithium transition metal oxide, which includes nickel, cobalt, and M elements. The M element includes manganese and / or aluminum. Based on the total molar number of nickel, cobalt, and M elements, the molar percentage of nickel is greater than or equal to 50% and less than 100%. The lithium transition metal oxide includes primary particles with a particle size of 0.5 μm to 6 μm. Based on the total number of primary particles with a particle size of 0.5 μm to 6 μm, the number of primary particles with a particle size of 0.5 μm to 2 μm accounts for 86% to 93%.
[0064] In this application, by controlling the molar proportion of nickel to be greater than or equal to 50% and less than 100%, the energy density of the secondary battery can be improved. By controlling the particle size of the primary particles within the above range, on the one hand, the diffusion distance of lithium ions can be shortened, the migration rate of lithium ions can be increased, and the kinetic performance of the secondary battery can be improved; on the other hand, the compaction density of the material can be increased, further improving the energy density of the secondary battery. In addition, based on the total number of primary particles with a particle size of 0.5μm to 6μm, the proportion of primary particles with a particle size of 0.5μm to 2μm in the cathode material is within the above range, reflecting that the particle size of the primary particles in the cathode material is mostly distributed between 0.5μm and 2μm, and the overall particle size of the cathode material is relatively small. This results in a shorter lithium ion transport path, which can further improve the kinetic performance of the cathode material, thereby increasing the energy density of the secondary battery.
[0065] For example, based on the total number of primary particles with a particle size of 0.5 μm to 6 μm, the percentage of primary particles with a particle size of 0.5 μm to 2 μm is a value between 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, or any combination thereof.
[0066] In this application, the term "primary particle" refers to a particle in the positive electrode film layer that has a complete boundary in the field of view under a certain magnification of a scanning electron microscope, such as 10,000x. The particle may contain pores and defects, but it does not have a complete boundary sufficient to divide it into two or more particles. The particle size of a primary particle refers to its longest diameter, which is the maximum spacing between all parallel lines in the two-dimensional projection of the particle.
[0067] In some embodiments, based on the total number of primary particles with a diameter of 0.5 μm to 6 μm, the proportion of primary particles with a diameter greater than 2 μm is 7% to 14%. A proportion of primary particles larger than 2 μm within this range reflects a lower number of larger particles in the cathode material, meaning the overall particle size of the cathode material is relatively small. This results in a shorter lithium-ion transport path, which is beneficial for reducing the internal resistance of the secondary battery, improving its kinetic performance, and thus increasing the battery's energy density. For example, based on the total number of primary particles with a diameter of 0.5 μm to 6 μm, the proportion of primary particles larger than 2 μm is a value within the range of 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or any combination thereof.
[0068] In some embodiments, based on the total number of primary particles with a diameter of 0.5 μm to 6 μm, the proportion of primary particles with a diameter greater than 3 μm is less than 5%. A proportion of primary particles larger than 3 μm within this range reflects a relatively small number of larger particles in the cathode material and a more concentrated particle size distribution, meaning the overall particle size of the cathode material is relatively small. This results in a shorter lithium-ion transport path, which is more conducive to improving the kinetic performance of the secondary battery, thereby further increasing the battery's energy density. For example, based on the total number of primary particles with a diameter of 0.5 μm to 6 μm, the proportion of primary particles larger than 3 μm is a value within the range of 4.99%, 4.5%, 4%, 3%, 2%, 1%, 0.5%, 0.1%, or any combination thereof.
[0069] In this application, the particle size distribution of the cathode material can be characterized using scanning electron microscopy (SEM) and particle size simulation software. Specifically, a secondary battery is disassembled to obtain the cathode electrode sheet. Cathode film powder is scraped off, and the powder is heat-treated to remove the conductive agent. The resulting powder and binder are then mixed in a certain proportion and added to the solvent N-methylpyrrolidone. The mixture is stirred evenly to form a cathode slurry. The cathode slurry is coated onto a cathode current collector, dried, and cold-pressed to obtain the cathode test electrode sheet. The cathode test electrode sheet is tested using SEM. The test sample and magnification are adjusted to include more than 100 primary particles in the field of view. Ten test images are selected at the same magnification to simulate particle size and obtain the particle size distribution of the primary particles in the cathode material.
[0070] In some embodiments, the cathode material is analyzed by X-ray diffraction to obtain the integrated area A of the (003) crystal plane. (003) The integral area A of the (101) crystal plane (101) The integral area A of the (012) crystal plane (012) And the integral area A of the (104) crystal plane (104) Satisfy: 20% ≤ A (104) / (A (003) +A (101) +A (012) +A (104) )≤50%, optionally, 30%≤A (104) / (A (003) +A (101) +A (012) +A (104)The X-ray diffraction pattern of the cathode material mainly contains four diffraction peaks, corresponding to the (003), (101), (012), and (104) crystal planes, respectively. Among them, the (003) and (101) crystal planes are not conducive to the insertion and extraction of lithium ions, and their electrochemical activity is low, while the (012) and (104) crystal planes can freely insert and extract lithium ions, and have higher electrochemical activity. The diffraction peaks of the (003), (101), (012), and (104) crystal planes are integrated to obtain the integrated area A corresponding to each crystal plane. (003) A (101) A (012) A (104) The integral area of each crystal face reflects the content of that crystal face, and the sum of the integral areas of the four crystal faces reflects the total content of crystal faces in the entire cathode material. A (104) / (A (003) +A (101) +A (012) +A (104) The (104) crystal plane represents the proportion of the (104) crystal plane in the entire cathode material. By controlling the proportion of the (104) crystal plane within the above range, the reversible insertion / extraction of lithium ions can be improved, thereby enhancing the kinetic performance of the secondary battery. For example, A... (104) / (A (003) +A (101) +A (012) +A (104) () is a value between 20%, 25%, 30%, 32%, 34%, 36%, 38%, 40%, 45%, 50%, or any combination of two of them.
[0071] In some embodiments, the cathode material is analyzed by X-ray diffraction to obtain the integrated area A of the (003) crystal plane. (003) The integral area A of the (101) crystal plane (101) The integral area A of the (012) crystal plane (012) And the integral area A of the (104) crystal plane (104) Satisfy: 3.5% ≤ A (012) / (A (003) +A (101) +A (012) +A (104) ≤5.5%, optionally, 4.0% ≤A (012) / (A (003) +A (101) +A (012) +A (104) ≤5.0%. A (012) / (A (003) +A (101) +A (012) +A(104) The (012) crystal plane represents the proportion of the (012) crystal plane in the entire cathode material. By controlling the proportion of the (012) crystal plane within the above range, the reversible insertion / extraction of lithium ions can be improved, thereby enhancing the kinetic performance of the secondary battery. For example, A... (012) / (A (003) +A (101) +A (012) +A (104) () is a value between 3.5%, 3.8%, 4.0%, 4.2%, 4.3%, 4.5%, 4.8%, 5.0%, 5.2%, 5.5%, or any combination of two of them.
[0072] In this application, the integrated areas of the (003), (104), (101), and (012) crystal planes can be determined by X-ray diffraction (XRD). Specifically, an X-ray powder diffractometer (Bruker D8ADVANCE, target material Cu Kα, voltage and current 40KV / 40mA, scanning angle range 10° to 70°) is used to test the cathode material and obtain its X-ray diffraction pattern. Then, the obtained X-ray diffraction pattern is refined and fitted to obtain the integrated area A of the (003) crystal plane. (003) The integral area A of the (101) crystal plane (101) The integral area A of the (012) crystal plane (012) And the integral area A of the (104) crystal plane (104) Then the proportion A of the (012) crystal plane is calculated. (012) / (A (003) +A (101) +A (012) +A (104) The proportion of the (104) crystal plane A (104) / (A (003) +A (101) +A (012) +A (104) ).
[0073] In some embodiments, the lithium transition metal oxide further includes a modifying element, which includes one or more of Mo, W, Nb, Sb, and V. Optionally, the modifying element includes Mo and / or W. The above-mentioned modifying elements can specifically adsorb on the (012) and (104) crystal planes, inhibiting the growth of the (012) and (104) crystal planes. In this way, the proportion of the (012) and (104) crystal planes can be controlled within the above-mentioned range, which is beneficial to the kinetic performance of the secondary battery.
[0074] In some embodiments, the mass percentage of the modifying element in the lithium transition metal oxide is 0.2% to 1%, optionally 0.3% to 0.8%. A mass percentage of the modifying element in the lithium transition metal oxide within the above range allows the proportions of the (012) and (104) crystal planes to be within the above range, which is beneficial for improving the kinetic performance of the secondary battery. Exemplarily, the mass percentage of the modifying element in the lithium transition metal oxide is a value within the range of 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or any combination thereof.
[0075] In this application, the mass percentage of modified elements in lithium transition metal oxide can be determined by inductively coupled plasma optical emission spectrometry (ICP). Specifically, 0.2 g of positive electrode active powder is weighed into a 100 mL beaker, 10 mL of 10% w / w nitric acid solution is added, and the mixture is heated and digested at 120 °C for 0.5 hours. The solution is then diluted to volume with a 100 mL volumetric flask. Another 1 mL of the diluted solution is pipetted into the 100 mL volumetric flask and diluted to volume to obtain the test solution. The mass fraction of each element in the test solution is determined using an inductively coupled plasma optical emission spectrometer (ICP-OES, Agilent 5800).
[0076] In some embodiments, when the negative electrode material of the lithium-ion secondary battery is graphite, when the lithium-ion secondary battery is charged and discharged at a current of 0.1C within a voltage range of 2.8V to 4.3V, the obtained capacity-voltage differential dQ / dV curve shows a first oxidation peak and a first reduction peak in the 3.60V to 3.80V range, and a second oxidation peak and a second reduction peak in the 4.15V to 4.25V range. In this application, the first oxidation peak and the first reduction peak represent the phase transition from H1 to M, and the second oxidation peak and the second reduction peak represent the phase transition from H2 to H3. The presence of the first oxidation peak, the first reduction peak, the second oxidation peak, and the second reduction peak in the dQ / dV curve reflects the existence of a reversible charge-discharge reaction in the positive electrode material, indicating that the positive electrode material has good structural stability.
[0077] In some embodiments, the absolute value ΔV1 of the difference between the peak voltage of the first oxidation peak and the peak voltage of the first reduction peak is less than or equal to 0.06V; and / or, the absolute value ΔV2 of the difference between the peak voltage of the second oxidation peak and the peak voltage of the second reduction peak is less than or equal to 0.08V. The small differences between the oxidation and reduction peaks in both voltage ranges indicate good electrochemical reversibility and low polarization of the cathode material, reflecting good kinetic performance of the secondary battery. For example, the absolute value ΔV1 of the difference between the peak voltage of the first oxidation peak and the peak voltage of the first reduction peak is a value within a range of 0.06V, 0.05V, 0.04V, 0.03V, 0.02V, 0.01V, or any two of them, and the absolute value ΔV2 of the difference between the peak voltage of the second oxidation peak and the peak voltage of the second reduction peak is a value within a range of 0.08V, 0.07V, 0.06V, 0.05V, 0.04V, 0.03V, 0.02V, 0.01V, or any two of them.
[0078] In some embodiments, the lithium-ion secondary battery includes a first voltage plateau at 3.60V to 3.80V; and / or, the lithium-ion secondary battery includes a second voltage plateau at 4.15V to 4.25V. Thus, the higher voltage plateau of the cathode material is beneficial for increasing the capacity of the secondary battery.
[0079] In some embodiments, the lithium-ion secondary battery includes one or more of the following features:
[0080] (1) Based on the total molar number of nickel, cobalt, and M elements, the molar percentage of nickel is 80% to 92%, optionally 80% to 88%. For example, the molar percentage of nickel is a value within a range of 80%, 82%, 84%, 86%, 88%, 90%, 92%, or any combination thereof. Therefore, a higher nickel content in the cathode material is beneficial for improving the energy density of the secondary battery.
[0081] (2) Based on the total molar number of nickel, cobalt, and M elements, the molar percentage of cobalt is 4% to 12%, optionally 4% to 9%. For example, the molar percentage of cobalt is a value within the range of 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, or any combination thereof. This allows for cost reduction without affecting the conductivity of the cathode material.
[0082] (3) Based on the total molar number of nickel, cobalt, and M, the molar percentage of M is 5% to 15%, optionally 9% to 12%. For example, the molar percentage of M is a value within the range of 5%, 7%, 9%, 10%, 12%, 15%, or any combination thereof. This is beneficial to the stability and safety performance of the secondary battery.
[0083] In some embodiments, the chemical formula of the lithium transition metal oxide includes: Li a Ni b Co c M d Q e O f Wherein, M includes Mn and / or Al, and Q includes one or more of Mo, W, Sb, Nb, and V; 0.8≤a≤1.1, 0.5≤b<1, 0.04≤c<1, 0.05≤d<1, 0.001≤e<1, 1.8≤f≤2.2, b+c+d+e=1, optionally, 0.8≤b≤0.92, 0.04≤c≤0.12, 0.05≤d≤0.15, 0.001≤e≤0.005, more optionally, 0.8≤b≤0.88, 0.04≤c≤0.09, 0.09≤d≤0.12, 0.002≤e≤0.005.
[0084] In this application, the role of element M is to improve the structural stability, cycle performance, and safety of lithium transition metal oxide materials. In ternary material systems, NCM (lithium nickel cobalt manganese oxide), NCA (lithium nickel cobalt aluminum oxide), and NCA (lithium nickel cobalt manganese aluminum oxide) have extremely similar properties. In practical applications, technicians can flexibly select element M as Mn, Al, or both, based on specific performance indicators, cost budgets, process conditions, and raw material supply, thereby achieving optimal matching of lithium transition metal oxide materials and meeting the diverse needs of different application scenarios.
[0085] In some implementations, the cathode material satisfies one or more of the following characteristics:
[0086] (1) 0.5μm ≤ Dv2 ≤ 1.4μm, where, for example, Dv2 is a value within the range of 0.5μm, 0.8μm, 1μm, 1.2μm, 1.4μm, or any two of these; (2) 2μm ≤ Dv50 ≤ 3μm, where, for example, Dv50 is a value within the range of 2μm, 2.2μm, 2.4μm, 2.6μm, 2.8μm, 3μm, or any two of these; (3) 7μm ≤ Dv99 ≤ 10μm, where, for example, Dv99 is a value within the range of 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, or any two of these. A particle size distribution within the above range is beneficial for balancing the capacity and cycle stability of the cathode material.
[0087] In this application, the volume distribution particle sizes Dv2, Dv50, and Dv99 of the cathode material are the particle sizes corresponding to a cumulative volume distribution percentage of 2%, 50%, and 99%, respectively, and can be determined using instruments and methods known in the art. For example, they can be determined using a laser particle size analyzer, referring to standard GB / T 19077-2016. The testing instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0088] In some implementations, the compaction density of the cathode material is 3.0 g / cm³ under a pressure of 4T. 3 ~3.4g / cm 3 A compaction density of the cathode material within the aforementioned range is beneficial for improving the energy density of lithium-ion secondary batteries. For example, the compaction density of the cathode material is 3.0 g / cm³. 3 3.1g / cm 3 3.2g / cm 3 3.3g / cm 3 3.4g / cm 3 Or the value between any two of them within a range.
[0089] In this application, the compaction density of the cathode material can be determined using instruments and methods known in the art. For example, it can be determined using an electronic pressure testing machine, referring to standard GB / T 24533-2009. The testing instrument can be a UTM7305 electronic pressure testing machine.
[0090] In some embodiments, the tap density of the cathode material is 1.4 g / cc to 1.8 g / cc. A tap density within this range is beneficial for controlling the gap between primary particles, ensuring close contact between them, and thus keeping the tap density of the cathode material within a suitable range, which is beneficial for improving the processing performance of the cathode sheet. For example, the tap density of the cathode material is a value within the range of 1.4 g / cc, 1.5 g / cc, 1.6 g / cc, 1.7 g / cc, 1.8 g / cc, or any combination thereof.
[0091] In this application, the tap density of the cathode material can be determined using instruments and methods known in the art. For example, it can be determined using a powder tap density tester, referring to standard GB / T 5162-2006. The testing instrument can be the Dandong Baite BT-301.
[0092] The cathode material in this application can be prepared, for example, by the following method: S1, preparing a precursor; in the precursor, based on the total molar number of metal elements in the precursor, the molar percentage of nickel element is greater than or equal to 50% and less than 100%; S2, after uniformly mixing the precursor and lithium source, sintering at 810℃~870℃ for 13h~17h in an oxygen atmosphere to obtain a sintered product; S3, pulverizing the sintered product to obtain the cathode material, the cathode material comprising primary particles with a particle size of 0.5μm~6μm, and based on the total number of primary particles with a particle size of 0.5μm~6μm, the proportion of primary particles with a particle size of 0.5μm~2μm is 86%~93%.
[0093] In this application, by controlling the temperature and time of the sintering process, the particle size of the primary particles can be controlled, ensuring that the particle size is within a suitable range. This shortens the diffusion distance of lithium ions, increases their migration rate, and improves the kinetic performance of the secondary battery. Furthermore, it increases the compaction density of the cathode material, which is beneficial for improving the energy density of the secondary battery. In addition, controlling the temperature and time of the sintering process also allows the proportion of primary particles with a particle size of 0.5 μm to 2 μm in the cathode material to be kept within a suitable range, resulting in a smaller overall particle size of the cathode material. This further improves the kinetic performance of the cathode material, thereby increasing the energy density of the battery.
[0094] In some implementations, the sintering process satisfies one or more of the following characteristics:
[0095] (1) Oxygen is used as the carrier gas; (2) The sintering temperature is 810℃~870℃. For example, the sintering temperature is a value between 810℃, 820℃, 830℃, 840℃, 850℃, 860℃, 870℃ or any combination thereof; (3) The sintering time is 13h~17h. For example, the sintering time is a value between 13h, 14h, 15h, 16h, 17h or any combination thereof. Sintering under the above conditions can make the particle size of the primary particles and the proportion of primary particles with a particle size of 0.5μm~2μm within a suitable range, which is beneficial to improving the dynamic performance of the secondary battery, thereby increasing the energy density of the battery.
[0096] In some embodiments, the molar ratio of the precursor to the lithium source is 1:(1.01 to 1.12). Exemplarily, the molar ratio of the precursor to the lithium source is a value between 1:1.01, 1:1.03, 1:1.05, 1:1.08, 1:1.1, 1:1.12, or any combination thereof.
[0097] In some embodiments, the precursor has the chemical formula including: Ni b Co c M d (OH)2, wherein 0.5≤b<1, 0.04≤c<1, 0.05≤d<1, optionally, 0.8≤b≤0.92, 0.04≤c≤0.12, 0.05≤d≤0.15, more optionally, 0.8≤b≤0.88, 0.04≤c≤0.09, 0.09≤d≤0.12; M includes Mn and / or Al.
[0098] In some embodiments, the lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, lithium oxide, lithium phosphate, lithium oxalate, lithium acetate, and lithium peroxide. Optionally, the lithium source is lithium hydroxide.
[0099] In some embodiments, step S2 further includes uniformly mixing the precursor, lithium source, and modification source at a molar ratio of 1:(1.01~1.12):(0.005~0.01), followed by the above-mentioned sintering treatment to obtain a sintered product. Thus, by adding a modification source during the sintering process, and setting the amount of modification source within a specific range, the proportions of the (012) and (104) crystal planes can be kept within a suitable range, thereby improving the kinetic performance of the secondary battery.
[0100] In some embodiments, the modification source includes one or more of Mo, W, Nb, Sb, V, and Mn sources. Thus, by adding specific modification sources during the sintering process, the proportions of the (012) and (104) crystal planes can be kept within a suitable range, thereby improving the reversible insertion / extraction of lithium ions and thus enhancing the kinetic performance of the secondary battery.
[0101] In some embodiments, the preparation process of the precursor in step S1 includes: mixing a nickel source, a cobalt source and an M source to form a metal salt solution, adding a precipitant and / or a complexing agent to the metal salt solution, controlling the pH value of the solution and the reaction temperature to carry out a co-precipitation reaction, and obtaining the precursor.
[0102] In some embodiments, the nickel source is a soluble nickel salt. Exemplarily, the nickel salt includes one or more of nickel sulfate, nickel nitrate, nickel chloride, nickel oxalate, and nickel acetate; optionally, the nickel source is nickel sulfate.
[0103] In some embodiments, the cobalt source is a soluble cobalt salt. Exemplarily, the cobalt salt includes one or more of cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt oxalate, and cobalt acetate; optionally, the cobalt source is cobalt sulfate.
[0104] In some implementations, the M source includes a manganese source and / or an aluminum source.
[0105] In some embodiments, the manganese source is a soluble manganese salt. Exemplarily, the manganese salt includes one or more of manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate, and manganese acetate; optionally, the manganese source is manganese sulfate.
[0106] In some embodiments, the aluminum source is a soluble aluminum salt. Exemplarily, the aluminum salt includes aluminum nitrate and / or sodium aluminate; optionally, the aluminum source is sodium aluminate.
[0107] In some embodiments, the precipitant includes one or more of sodium hydroxide, sodium carbonate, potassium hydroxide, potassium carbonate, and lithium hydroxide; optionally, the precipitant is sodium hydroxide.
[0108] In some embodiments, the complexing agent includes one or more of ammonia, ammonium chloride, ammonium sulfate, urea, citric acid, and ethylenediaminetetraacetic acid (EDTA), and optionally, the complexing agent is ammonia.
[0109] In some embodiments, the molar ratio of the nickel source, cobalt source, and manganese source is b:c:d, wherein 0.5≤b<1, 0.04≤c<1, 0.05≤d<1; optionally, 0.8≤b≤0.92, 0.04≤c≤0.12, 0.05≤d≤0.15, 0.04≤c≤0.12, 0.05≤d≤0.15; more preferably, 0.8≤b≤0.88, 0.04≤c≤0.09, 0.09≤d≤0.12.
[0110] In some implementations, the coprecipitation reaction satisfies one or more of the following characteristics:
[0111] (1) The reaction temperature is 55℃~65℃, for example, the reaction temperature is a value between 55℃, 58℃, 60℃, 62℃, 65℃ or any two of them; (2) The reaction time is 45h~50h, for example, the reaction time is a value between 45h, 46h, 47h, 48h, 49h, 50h or any two of them; (3) The reaction pH value is 10~11, for example, the reaction pH value is a value between 10, 10.2, 10.4, 10.6, 10.8, 11 or any two of them; (4) The concentration of the complexing agent is 4g / L~6g / L, for example, the concentration of the complexing agent is a value between 4g / L, 4.5g / L, 5g / L, 5.5g / L, 6g / L or any two of them.
[0112] The term "secondary battery" used in this article refers to a single battery cell, a battery module, or a battery pack. These will be explained separately below.
[0113] Typically, a single secondary battery cell includes a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and releasing. The electrolyte acts as a conductor between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.
[0114] Negative electrode sheet
[0115] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.
[0116] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0117] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0118] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0119] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0120] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0121] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0122] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0123] Positive electrode sheet
[0124] The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector, wherein the positive electrode film layer includes the positive electrode material of this application.
[0125] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0126] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0127] During the charging and discharging process of a battery, Li undergoes insertion / extraction and consumption, resulting in varying molar Li content at different discharge states. In the examples of positive electrode active materials in this application, the molar Li content refers to the initial state of the material, i.e., before feeding. When the positive electrode active material is applied to the battery system, the molar Li content changes after charge-discharge cycles.
[0128] In the examples of positive electrode active materials in this application, the molar content of O is only a theoretical value. Oxygen release from the crystal lattice will cause changes in the molar content of oxygen, and the actual molar content of O will fluctuate.
[0129] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0130] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0131] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0132] electrolytes
[0133] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.
[0134] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0135] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0136] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0137] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0138] Separating membrane
[0139] In some embodiments, the battery cell also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.
[0140] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0141] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.
[0142] In some embodiments, the battery cell may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.
[0143] In some embodiments, the outer packaging of the battery cell can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the battery cell can also be a flexible package, such as a pouch. The material of the flexible package can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0144] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 The example shown is a square-structured battery cell 5.
[0145] In some implementations, refer to Figure 2 The outer packaging may include a housing 51 and a top cover assembly 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the top cover assembly 53 can cover the opening to close the receiving cavity. A positive electrode sheet, a negative electrode sheet, and a separator can be formed into an electrode assembly 52 through a winding process or a stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The number of electrode assemblies 52 contained in a single battery cell 5 can be one or more, which can be selected by those skilled in the art according to specific practical needs.
[0146] In some implementations, individual battery cells can be assembled into a battery module. The number of individual battery cells contained in a battery module can be one or more, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery module.
[0147] Figure 3 This is battery module 4, used as an example. (See reference...) Figure 3 In battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.
[0148] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.
[0149] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0150] Figure 4 and Figure 5 This is battery pack 1 as an example. (See reference...) Figure 4 and Figure 5 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0151] Electrical appliances
[0152] The second aspect of this application provides an electrical device, which includes the lithium-ion secondary battery provided in the first aspect of this application.
[0153] Secondary batteries can be used as a power source for electrical devices or as an energy storage unit for electrical devices. Electrical devices can include, but are not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0154] As an electrical device, you can choose individual battery cells, battery modules, or battery packs according to your usage requirements.
[0155] Figure 6 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery for this device, a battery pack or battery module can be used.
[0156] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.
[0157] cathode materials
[0158] A third aspect of this application provides a cathode material comprising a lithium transition metal oxide, wherein the lithium transition metal oxide comprises nickel, cobalt, and M, wherein the M comprises manganese and / or aluminum, and the molar percentage of nickel is greater than or equal to 50% and less than 100% based on the total molar number of nickel, cobalt, and M, and the lithium transition metal oxide comprises primary particles with a particle size of 0.5 μm to 6 μm, wherein the number of primary particles with a particle size of 0.5 μm to 2 μm accounts for 86% to 93% based on the total number of primary particles with a particle size of 0.5 μm to 6 μm.
[0159] In this application, by controlling the nickel content to be greater than or equal to 50% and less than 100%, the energy density of the secondary battery can be improved. By controlling the particle size of the primary particles within the above range, on the one hand, the diffusion distance of lithium ions can be shortened, the migration rate of lithium ions can be increased, and the kinetic performance of the secondary battery can be improved; on the other hand, the compaction density of the material can be increased, further improving the energy density of the secondary battery. In addition, the proportion of primary particles with a particle size of 0.5μm to 2μm in the cathode material is within the above range, reflecting that the particle size of the primary particles in the cathode material is mostly distributed between 0.5μm and 2μm, and the overall particle size of the cathode material is relatively small. This results in a shorter lithium ion transport path, which can further improve the kinetic performance of the cathode material, thereby increasing the energy density of the secondary battery.
[0160] In some implementations, based on the total number of primary particles with a diameter of 0.5 μm to 6 μm, the proportion of primary particles with a diameter greater than 2 μm is 7% to 14%. This reflects that there are fewer particles with larger diameters in the cathode material, that is, the overall particle size of the cathode material is relatively small, which is beneficial to reducing the internal resistance of the secondary battery, improving the dynamic performance of the secondary battery, and thus improving the energy density of the battery.
[0161] In some implementations, based on the total number of primary particles with a diameter of 0.5 μm to 6 μm, the proportion of primary particles with a diameter greater than 3 μm is less than 5%. This reflects that there are fewer particles with larger diameters in the cathode material and the particle size distribution is more concentrated, meaning that the overall particle size of the cathode material is relatively small, which is more conducive to improving the kinetic performance of the secondary battery, thereby further improving the energy density of the battery.
[0162] In some embodiments, the cathode material is analyzed by X-ray diffraction to obtain the integrated area A of the (003) crystal plane. (003) The integral area A of the (101) crystal plane (101) The integral area A of the (012) crystal plane (012) And the integral area A of the (104) crystal plane (104) Satisfy: 20% ≤ A (104) / (A (003) +A (101) +A (012) +A (104) )≤50%, optionally, 30%≤A (104) / (A (003) +A (101) +A (012) +A (104) The proportion of (104) crystal planes is ≤40%. By controlling the proportion of (104) crystal planes within the above range, the reversible insertion and extraction of lithium ions can be improved, thereby improving the kinetic performance of secondary batteries.
[0163] In some embodiments, the cathode material is analyzed by X-ray diffraction to obtain the integrated area A of the (003) crystal plane. (003) The integral area A of the (101) crystal plane (101) The integral area A of the (012) crystal plane (012) And the integral area A of the (104) crystal plane (104) Satisfy: 3.5% ≤ A (012) / (A (003) +A (101) +A (012) +A (104) ≤5.5%, optionally, 4.0% ≤A (012) / (A (003) +A (101) +A (012) +A (104) The proportion of (012) crystal planes is ≤5.0%. By controlling the proportion of (012) crystal planes within the above range, the reversible insertion and extraction of lithium ions can be improved, thereby improving the kinetic performance of secondary batteries.
[0164] In some embodiments, the lithium transition metal oxide further includes a modifying element, which includes one or more of Mo, W, Nb, Sb, and V. Optionally, the modifying element includes Mo and / or W. The above-mentioned modifying elements can specifically adsorb on the (012) and (104) crystal planes, inhibiting the growth of the (012) and (104) crystal planes, thereby controlling the proportion of the (012) and (104) crystal planes within the above-mentioned ranges, which is beneficial to the kinetic performance of the secondary battery.
[0165] In some embodiments, the modified element has a mass percentage of 0.2% to 1% in the lithium transition metal oxide, and optionally, 0.3% to 0.8%. This allows the proportions of the (012) and (104) crystal planes to be within the above range, which is beneficial to improving the kinetic performance of the secondary battery.
[0166] In some embodiments, when a lithium-ion secondary battery assembled from a cathode material and graphite is charged and discharged at a current of 0.1C within a voltage range of 2.8V to 4.3V, the obtained capacity-voltage differential dQ / dV curve exhibits a first oxidation peak and a first reduction peak in the 3.60V to 3.80V range, and a second oxidation peak and a second reduction peak in the 4.15V to 4.25V range. Therefore, the presence of the first oxidation peak, the first reduction peak, the second oxidation peak, and the second reduction peak in the dQ / dV curve reflects a reversible charge-discharge reaction of the cathode material, indicating that the cathode material possesses good structural stability.
[0167] In some embodiments, the absolute value ΔV1 of the difference between the peak voltage of the first oxidation peak and the peak voltage of the first reduction peak is less than or equal to 0.06V; and / or, the absolute value ΔV2 of the difference between the peak voltage of the second oxidation peak and the peak voltage of the second reduction peak is less than or equal to 0.08V. The small differences between the oxidation and reduction peaks in both voltage ranges indicate good electrochemical reversibility and low polarization of the cathode material, reflecting good kinetic performance of the secondary battery.
[0168] In some embodiments, the lithium-ion secondary battery includes a first voltage plateau at 3.60V to 3.80V; and / or, the lithium-ion secondary battery includes a second voltage plateau at 4.15V to 4.25V. Thus, the higher voltage plateau of the cathode material is beneficial for increasing the capacity of the secondary battery.
[0169] In some embodiments, the lithium-ion secondary battery includes one or more of the following features:
[0170] (1) Based on the total molar number of nickel, cobalt, and M elements, the molar proportion of nickel is 80% to 92%, and optionally 80% to 88%. Therefore, the high nickel content in the cathode material is beneficial to improving the energy density of the secondary battery;
[0171] (2) Based on the total molar number of nickel, cobalt, and M elements, the molar proportion of cobalt is 4% to 12%, optionally 4% to 9%. Therefore, cost reduction can be achieved without affecting the conductivity of the cathode material;
[0172] (3) Based on the total molar number of nickel, cobalt and M elements, the molar percentage of M element is 5% to 15%, and optionally 9% to 12%. This is beneficial to the stability and safety performance of the secondary battery.
[0173] In some embodiments, the chemical formula of the lithium transition metal oxide includes: Li a Ni b Co c M d Q e O f Wherein, M includes Mn and / or Al, and Q includes one or more of Mo, W, Sb, Nb, and V; 0.8≤a≤1.1, 0.5≤b<1, 0.04≤c<1, 0.05≤d<1, 0.001≤e<1, 1.8≤f≤2.2, b+c+d+e=1, optionally, 0.8≤b≤0.92, 0.04≤c≤0.12, 0.05≤d≤0.15, 0.001≤e≤0.005, more optionally, 0.8≤b≤0.88, 0.04≤c≤0.09, 0.09≤d≤0.12, 0.002≤e≤0.005.
[0174] In some implementations, the cathode material satisfies one or more of the following characteristics:
[0175] (1) 0.5μm≤Dv2≤1.4μm; (2) 2μm≤Dv50≤3μm; (3) 7μm≤Dv99≤10μm. A particle size distribution within the above range is beneficial for balancing the capacity and cycle stability of the cathode material.
[0176] In some implementations, the compaction density of the cathode material is 3.0 g / cm³ under a pressure of 4T. 3 ~3.4g / cm 3 A compaction density of the cathode material within the aforementioned range is beneficial for improving the energy density of lithium-ion secondary batteries.
[0177] In some embodiments, the tap density of the positive electrode material is 1.4 g / cc to 1.8 g / cc. A tap density within this range is beneficial for improving the processing performance of the positive electrode sheet.
[0178] Example
[0179] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0180] Example 1
[0181] Preparation of cathode materials:
[0182] S1, nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.82:0.08:0.10 to prepare a sulfate solution. Under a nitrogen atmosphere, sodium hydroxide solution was added to adjust the pH of the sulfate solution to 10, and 4 g / L ammonia water was added. The reaction was carried out at 60 °C for 48 h to prepare the precursor Ni. 0.82 Co 0.08 Mn 0.10 (OH)2, precursor Ni 0.82 Co 0.08 Mn 0.10 The volumetric particle size Dv50 of (OH)2 is 3 μm;
[0183] S2, the precursor Ni 0.82 Co 0.08 Mn 0.10(OH)2 and LiOH·H2O were mixed at a molar ratio of 1:1.02 and then reacted at 850℃ under pure oxygen conditions for 15 h to obtain the sintered product.
[0184] S3, the sintered product is subjected to air jet milling to obtain the cathode material LiNi. 0.82 Co 0.08 Mn 0.10 O2.
[0185] Cathode material parameter testing:
[0186] (1) Particle size testing of cathode materials
[0187] The positive electrode material and binder from Example 1 were mixed in a certain proportion and then added to the solvent N-methylpyrrolidone. The mixture was stirred until homogeneous to form a positive electrode slurry. This slurry was coated onto the positive electrode current collector, dried, and cold-pressed to obtain the positive electrode sheet. The positive electrode sheet was tested using a scanning electron microscope. The test sample and magnification were adjusted to include more than 100 primary particles in the field of view. Ten test images were selected at the same magnification, and particle size simulation software was used to simulate the particle size distribution of the primary particles in the positive electrode material. The test results showed that the particle size distribution of the positive electrode material in Example 1 was mainly concentrated in the range of 0.5 μm to 2 μm, indicating that the particle size of the positive electrode material was relatively small. Furthermore, the particle size range of the primary particles in the positive electrode material, as well as the percentage of primary particles with a diameter of 0.5 μm to 2 μm, a diameter greater than 2 μm, and a diameter greater than 3 μm, are recorded in Table 1 below.
[0188] (2) Volume distribution particle size test
[0189] The volumetric particle size distribution of the cathode material was tested using a Malvern 2000 (MasterSizer 2000) laser particle size analyzer, following the standard procedure GB / T19077-2016 / ISO 13320:2009. In Example 1, the volumetric particle sizes of the cathode material were Dv2 0.74 μm, Dv50 2.8 μm, and Dv99 7.7 μm.
[0190] (3) Tap density test
[0191] Using a Dandong BT-300 graduated cylinder and a 25mL graduated cylinder, the positive electrode material was filled to 20mL. The cylinder was then vibrated 5000 times at a frequency of 250 times / min and an amplitude of 3.0mm. The tap density of the positive electrode material was measured. In Example 1, the tap density of the positive electrode material was 1.5g / cc.
[0192] (4) Compacted density test
[0193] The compaction density of the cathode material was determined using an electronic pressure testing machine (UTM7305 type) according to the standard procedure GB / T24533-2009. An exemplary test method is as follows: Weigh 1g of cathode material powder and add it to a container with a bottom area of 1.327cm². 2 In the mold, pressure was applied to 4T and held for 30s, then the pressure was released and held for 10s. The compaction density of the cathode material under 4T pressure was then recorded and calculated. In Example 1, the compaction density of the cathode material under 4T pressure was 3.3 g / cm³. 3 .
[0194] (5) Scanning electron microscopy (SEM) test
[0195] The cathode material was tested using SEM to obtain its microstructure.
[0196] Figure 7 This is a scanning electron microscope image of the positive electrode material in Example 1, such as... Figure 7 As shown, the cathode material is in the form of dispersed primary particles or a small number of primary particles aggregated together, with a particle size of 0.6 μm to 5.4 μm.
[0197] Preparation of lithium-ion secondary batteries
[0198] (1) Preparation of positive electrode sheet
[0199] The prepared positive electrode material, polyvinylidene fluoride, conductive carbon black, and sodium carboxymethyl cellulose were mixed in a weight ratio of 95:1.5:2.5:1 and then added to the solvent N-methylpyrrolidone. The mixture was stirred evenly to form a positive electrode slurry. The positive electrode slurry was coated onto the positive electrode current collector aluminum foil to form a positive electrode film. After drying and cold pressing, the positive electrode sheet was obtained.
[0200] (2) Preparation of negative electrode sheet
[0201] The negative electrode materials, silicon-carbon composite (silicon accounts for 5 wt%), silicon suboxide, sodium carboxymethyl cellulose, styrene-butadiene rubber, and acetylene black, are thoroughly mixed in an appropriate amount of deionized water at a weight ratio of 89:7:1:1:2 to form a negative electrode slurry. The negative electrode slurry is coated onto an 8 μm thick copper foil to form a negative electrode film. After drying and cold pressing, a negative electrode sheet is obtained.
[0202] (3) Preparation of electrolyte
[0203] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3:7 to form an organic solvent. LiPF6 was then dissolved in the organic solvent to obtain an electrolyte with a LiPF6 concentration of 1 mol / L.
[0204] (4) Separating membrane
[0205] A polyethylene-based membrane is used as the separator, with boehmite coated on the surface, and the separator thickness is 7μm.
[0206] (5) Preparation of lithium-ion secondary batteries
[0207] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide insulation. The electrode assembly is then formed by bending and winding. The electrode assembly is placed in outer packaging, dried, and then injected with the prepared electrolyte. After vacuum sealing, settling, formation, and shaping, a lithium-ion secondary battery is obtained.
[0208] Performance testing of lithium-ion secondary batteries:
[0209] (1) Dynamic performance test
[0210] 1) DCR test
[0211] At 25℃, the lithium-ion secondary battery was charged at a constant current of 0.33C to the cutoff voltage of 4.3V, and then charged at a constant voltage of 4.3V to a current of 0.05C, at which point the secondary battery was fully charged. After the fully charged secondary battery was left to stand for 5 minutes, it was discharged at a current of 0.33C to 90% SOC, and the voltage V1 was recorded. Then it was discharged at a current of 4C for 30 seconds, and the voltage V2 was recorded. The battery charge-discharge internal resistance DCR = (V2-V1) / current was calculated, and the test results are recorded in Table 2 below.
[0212] 2) Capacity-voltage differential (dQ / dV) curve analysis
[0213] At 25°C, the lithium-ion secondary battery was charged at a constant current of 0.1C to 4.3V within a voltage range of 2.8V to 4.3V. Then, it was charged at a constant voltage of 4.3V until the current reached 0.05C, and the charging capacity of the lithium-ion secondary battery was recorded. Then, it was discharged at a constant current of 0.1C until the lower limit voltage reached 2.8V, and the discharge capacity of the lithium-ion secondary battery was recorded. The QV curve of capacity and voltage, as well as the capacity-voltage differential and the dQ / dV-V curve of voltage, were obtained.
[0214] Figure 8 The dQ / dV curves of the lithium-ion secondary battery in Example 1 show that the lithium-ion secondary battery has a first oxidation peak and a first reduction peak in the range of 3.60V to 3.80V, and a second oxidation peak and a second reduction peak in the range of 4.15V to 4.25V. The absolute value of the difference between the peak voltage of the first oxidation peak and the peak voltage of the first reduction peak, ΔV1, is 0.02V, and the absolute value of the difference between the peak voltage of the second oxidation peak and the peak voltage of the second reduction peak, ΔV2, is also 0.02V. The test results are recorded in Table 2 below.
[0215] (2) Energy density test
[0216] ① At 25℃, the lithium-ion secondary battery is charged at a constant current of 0.33C to a cutoff voltage of 4.3V, and then charged at a constant voltage of 4.3V until the current is 0.05C. At this point, the secondary battery is fully charged. After the fully charged secondary battery is left to stand for 5 minutes, it is discharged at a constant current of 0.33C to a cutoff voltage of 2.8V. The discharge capacity at this point is the actual capacity of the secondary battery at 0.33C, denoted as C0.
[0217] ②Then, the secondary battery is charged at a constant current of 0.33C0 to the cutoff voltage of 4.3V, and then charged at a constant voltage until the current is 0.05C. At this point, the secondary battery is fully charged. After the fully charged secondary battery is left to stand for 5 minutes, it is discharged at a constant current of 0.33C0 to the cutoff voltage of 2.8V, and the discharge energy Q of the secondary battery is obtained. The energy density of the secondary battery (Wh / Kg) = discharge energy Q of the secondary battery / mass M of the active material of the secondary battery. The test results are recorded in Table 2 below.
[0218] Examples 2 to 4
[0219] The lithium-ion secondary battery was prepared using the same method as in Example 1, except that the sintering temperature and sintering time during the sintering process were adjusted according to Table 1 below.
[0220] Comparative Example 1
[0221] The lithium-ion secondary battery was prepared using the same method as in Example 1, except that the sintering temperature and sintering time during the sintering process were adjusted according to Table 1 below, so that in the prepared cathode material, based on the total number of primary particles with a particle size of 0.5 μm to 6 μm, the proportion of primary particles with a particle size of 0.5 μm to 2 μm was 44%.
[0222] The particle size and particle size distribution of the primary particles in the cathode materials prepared in Examples 2 to 4 and Comparative Example 1 were determined according to the same test method as in Example 1, and the performance of the lithium-ion secondary batteries prepared in Examples 2 to 4 and Comparative Example 1 were tested according to the same test method as in Example 1.
[0223] Table 1 below shows the relevant parameters of the cathode materials prepared in Examples 1 to 4 and Comparative Example 1. Table 2 below shows the performance test results of the lithium-ion secondary batteries prepared in Examples 1 to 4 and Comparative Example 1.
[0224] Table 1
[0225]
[0226] Table 2
[0227]
[0228] As can be seen from Tables 1 and 2, compared with Comparative Example 1 (where the proportion of primary particles with a particle size of 0.5 μm to 2 μm is less than 86%), Examples 1 to 4, by controlling the sintering temperature to 810℃ to 870℃ and the sintering time to 13h to 17h, resulted in a primary particle size of 0.5 μm to 6 μm in the lithium transition metal oxide, and a proportion of primary particles with a particle size of 0.5 μm to 2 μm of 86% to 93% based on the total number of primary particles with a particle size of 0.5 μm to 6 μm, which significantly improved the kinetic performance and energy density of the secondary battery.
[0229] Example 5
[0230] A lithium-ion secondary battery was prepared using the same method as in Example 1, except that steps S2 and S3 were performed as follows: Ni precursor was... 0.82 Co 0.08 Mn 0.10 (OH)₂, LiOH·H₂O, and MoO were mixed in a molar ratio of 1:1.02:0.003, and then reacted at 850℃ under pure oxygen conditions for 15 h to obtain a sintered product. The sintered product was then subjected to air jet milling to obtain the cathode material LiNi. 0.82 Co 0.08 Mn 0.10 Mo 0.003 O2.
[0231] Example 6
[0232] A lithium-ion secondary battery was prepared using the same method as in Example 1, except that steps S2 and S3 were performed as follows: Ni precursor was... 0.82 Co 0.08 Mn 0.10 (OH)₂, LiOH·H₂O, and WO₃ were mixed in a molar ratio of 1:1.02:0.003, and then reacted at 850℃ under pure oxygen conditions for 15 h to obtain a sintered product. The sintered product was then subjected to air jet milling to obtain the cathode material LiNi. 0.82 Co 0.08 Mn 0.10 W 0.003 O2.
[0233] Example 7
[0234] A lithium-ion secondary battery was prepared using the same method as in Example 1, except that steps S2 and S3 were performed as follows: Ni precursor was... 0.82 Co 0.08 Mn 0.10(OH)₂, LiOH·H₂O, and SbO₂ were mixed in a molar ratio of 1:1.02:0.003, and then reacted at 850℃ under pure oxygen conditions for 15 h to obtain a sintered product. The sintered product was then subjected to air jet milling to obtain the cathode material LiNi. 0.82 Co 0.08 Mn 0.10 Sb 0.003 O2.
[0235] Cathode material parameter testing:
[0236] (1) Testing of different crystal plane ratios
[0237] The cathode material was tested using an X-ray powder diffractometer (instrument model: Bruker D8 ADVANCE, target material: Cu Kα; voltage and current: 40KV / 40mA; scanning angle range: 10° to 70°). The obtained X-ray diffraction patterns were refined and fitted to obtain the integrated areas A of the (003), (101), (012), and (104) crystal planes. (003) A (101) A (012) A (104) Then calculate the proportion A of the (012) crystal plane. (012) / (A (003) +A (101) +A (012) +A (104) The proportion of the (104) crystal plane A (104) / (A (003) +A (101) +A (012) +A (104) The test results of Examples 5 to 7 are recorded in Table 3 below.
[0238] (2) Modified element content test
[0239] Weigh 0.2g of positive electrode active powder into a 100mL beaker, add 10mL of 10% w / w nitric acid solution, heat and digest at 120℃ for 0.5 hours, then dilute to volume with a 100mL volumetric flask, and then use a pipette to transfer 1mL to a 100mL volumetric flask and dilute to volume to obtain the test solution.
[0240] The mass fraction of the modified elements in the test solution was determined using an inductively coupled plasma optical emission spectrometer (ICP-OES, instrument brand: Agilent 5800). The ICP test results showed that the mass percentage of Mo in the cathode material of Example 5 was 0.3%, the mass percentage of W in the cathode material of Example 6 was 0.3%, and the mass percentage of Sb in the cathode material of Example 7 was 0.3%.
[0241] The particle size and particle size distribution of the primary particles in the cathode materials prepared in Examples 5 to 7 were determined according to the same test method as in Example 1, and the performance of the lithium-ion secondary batteries prepared in Examples 5 to 7 was tested according to the same test method as in Example 1.
[0242] Table 3 below shows the relevant parameters of the cathode materials prepared in Examples 5 to 7. Table 4 below shows the performance test results of the lithium-ion secondary batteries prepared in Examples 5 to 7.
[0243] Table 3
[0244]
[0245] Table 4
[0246]
[0247] As can be seen from Tables 3 and 4, by adding the modifying elements Mo, W, and Sb in Examples 5 to 7, the particle size of the primary particles in the lithium transition metal oxide can be made to be 0.5 μm to 6 μm, and the proportion of primary particles with a particle size of 0.5 μm to 2 μm is 86% to 93% based on the total number of primary particles with a particle size of 0.5 μm to 6 μm, which significantly improves the kinetic performance and energy density of the secondary battery.
[0248] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A lithium-ion secondary battery, characterized in that, The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector and comprising a positive electrode material. The cathode material comprises a lithium transition metal oxide, which includes nickel, cobalt, and element M. Element M includes manganese and / or aluminum. Based on the total molar number of nickel, cobalt, and element M, the molar percentage of nickel is greater than or equal to 50% and less than 100%. The lithium transition metal oxide comprises primary particles with a particle size of 0.5 μm to 6 μm, and based on the total number of primary particles with a particle size of 0.5 μm to 6 μm, the proportion of primary particles with a particle size of 0.5 μm to 2 μm is 86% to 93%.
2. The lithium-ion secondary battery according to claim 1, characterized in that, Based on the total number of primary particles with a diameter of 0.5 μm to 6 μm, the proportion of primary particles with a diameter greater than 2 μm is 7% to 14%.
3. The lithium-ion secondary battery according to claim 1 or 2, characterized in that, Based on the total number of primary particles with a diameter of 0.5μm to 6μm, the proportion of primary particles with a diameter greater than 3μm is less than 5%.
4. The lithium-ion secondary battery according to any one of claims 1 to 3, characterized in that, The lithium transition metal oxide further includes modifying elements, which include one or more of Mo, W, Nb, Sb, and V.
5. The lithium-ion secondary battery according to claim 4, characterized in that, The modifying element accounts for 0.2% to 1% of the mass of the lithium transition metal oxide.
6. The lithium-ion secondary battery according to any one of claims 1 to 5, characterized in that, The cathode material was analyzed by X-ray diffraction, and the integral area A of the (003) crystal plane was obtained. (003) The integral area A of the (101) crystal plane (101) The integral area A of the (012) crystal plane (012) And the integral area A of the (104) crystal plane (104) Satisfy: 20% ≤ A (104) / (A (003) +A (101) +A (012) +A (104) ≤50%.
7. The lithium-ion secondary battery according to any one of claims 1 to 6, characterized in that, The cathode material was analyzed by X-ray diffraction, and the integral area A of the (003) crystal plane was obtained. (003) The integral area A of the (101) crystal plane (101) The integral area A of the (012) crystal plane (012) And the integral area A of the (104) crystal plane (104) Satisfy: 3.5% ≤ A (012) / (A (003) +A (101) +A (012) +A (104) ≤5.5%.
8. The lithium-ion secondary battery according to any one of claims 1 to 7, characterized in that, When the negative electrode material of the lithium-ion secondary battery is graphite, when the lithium-ion secondary battery is charged and discharged at a current of 0.1C in the voltage range of 2.8V to 4.3V, the obtained capacity-voltage differential dQ / dV curve has a first oxidation peak and a first reduction peak in the range of 3.60V to 3.80V, and the capacity-voltage differential dQ / dV curve has a second oxidation peak and a second reduction peak in the range of 4.15V to 4.25V.
9. The lithium-ion secondary battery according to claim 8, characterized in that, The absolute value of the difference between the peak voltage of the first oxidation peak and the peak voltage of the first reduction peak, ΔV1, is less than or equal to 0.06V; and / or, The absolute value of the difference between the peak voltage of the second oxidation peak and the peak voltage of the second reduction peak, ΔV2, is less than or equal to 0.08V.
10. The lithium-ion secondary battery according to any one of claims 1 to 9, characterized in that, Includes one or more of the following features: (1) Based on the total number of moles of nickel, cobalt and M, the molar percentage of nickel is 80% to 92%; (2) Based on the total number of moles of nickel, cobalt, and M, the molar percentage of cobalt is 4% to 12%; (3) Based on the total number of moles of nickel, cobalt and M, the molar percentage of M is 5% to 15%.
11. The lithium-ion secondary battery according to any one of claims 1 to 10, characterized in that, The cathode material satisfies one or more of the following characteristics: (1) 0.5μm≤Dv2≤1.4μm; (2) 2μm≤Dv50≤3μm; (3) 7μm≤Dv99≤10μm.
12. The lithium-ion secondary battery according to any one of claims 1 to 11, characterized in that, Under a pressure of 4T, the compaction density of the cathode material is 3.0 g / cm³. 3 ~3.4g / cm 3 ; and / or, the tap density of the positive electrode material is 1.4 g / cc to 1.8 g / cc.
13. An electrical appliance, characterized in that, The lithium-ion secondary battery includes any one of claims 1 to 12.
14. A positive electrode material, characterized in that, The lithium transition metal oxide includes nickel, cobalt, and element M, wherein element M includes manganese and / or aluminum, and the molar percentage of nickel is greater than or equal to 50% and less than 100% based on the total molar number of nickel, cobalt, and element M. The lithium transition metal oxide comprises primary particles with a particle size of 0.5 μm to 6 μm, and based on the total number of primary particles with a particle size of 0.5 μm to 6 μm, the proportion of primary particles with a particle size of 0.5 μm to 2 μm is 86% to 93%.
15. The cathode material according to claim 14, characterized in that, Based on the total number of primary particles with a diameter of 0.5 μm to 6 μm, the proportion of primary particles with a diameter greater than 2 μm is 7% to 14%; and / or, Based on the total number of primary particles with a diameter of 0.5μm to 6μm, the proportion of primary particles with a diameter greater than 3μm is less than 5%.
16. The cathode material according to claim 14 or 15, characterized in that, The lithium transition metal oxide further includes modifying elements, which include one or more of Mo, W, Nb, Sb, and V.
17. The cathode material according to claim 16, characterized in that, The modifying element accounts for 0.2% to 1% of the mass of the lithium transition metal oxide.
18. The cathode material according to any one of claims 14 to 17, characterized in that, The cathode material was analyzed by X-ray diffraction, and the integral area A of the (003) crystal plane was obtained. (003) The integral area A of the (101) crystal plane (101) The integral area A of the (012) crystal plane (012) And the integral area A of the (104) crystal plane (104) Satisfy: 20% ≤ A (104) / (A (003) +A (101) +A (012) +A (104) ≤50%, sum / or,3.5%≤A (012) / ( A (003) +A (101) +A (012) +A (104) ) ≤ 5.5%.
19. The cathode material according to any one of claims 14 to 18, characterized in that, When the lithium-ion secondary battery assembled from the cathode material and graphite is charged and discharged at a current of 0.1C within a voltage range of 2.8V to 4.3V, the obtained capacity-voltage differential dQ / dV curve shows a first oxidation peak and a first reduction peak in the range of 3.60V to 3.80V, and the capacity-voltage differential dQ / dV curve shows a second oxidation peak and a second reduction peak in the range of 4.15V to 4.25V.
20. The cathode material according to claim 19, characterized in that, The absolute value of the difference between the peak voltage of the first oxidation peak and the peak voltage of the first reduction peak, ΔV1, is less than or equal to 0.06V; and / or, The absolute value of the difference between the peak voltage of the second oxidation peak and the peak voltage of the second reduction peak, ΔV2, is less than or equal to 0.08V.
21. The cathode material according to any one of claims 14 to 20, characterized in that, Includes one or more of the following features: (1) Based on the total number of moles of nickel, cobalt and M, the molar percentage of nickel is 80% to 92%; (2) Based on the total number of moles of nickel, cobalt, and M, the molar percentage of cobalt is 4% to 12%; (3) Based on the total number of moles of nickel, cobalt and M, the molar percentage of M is 5% to 15%.
22. The cathode material according to any one of claims 14 to 21, characterized in that, The cathode material satisfies one or more of the following characteristics: (1) 0.5μm≤Dv2≤1.4μm; (2) 2μm≤Dv50≤3μm; (3) 7μm≤Dv99≤10μm.
23. The cathode material according to any one of claims 14 to 22, characterized in that, Under a pressure of 4T, the compaction density of the cathode material is 3.0 g / cm³. 3 ~3.4g / cm 3 ; and / or, The tap density of the positive electrode material is 1.4 g / cc to 1.8 g / cc.